A Normative Legal Study on PELAJAR Design in Gresik Regency - Suyanto Suyanto; Riski Dwi Prameswari; Devy Syanindita Roshida; Nafiatus Sintya Deviatin; Ika Ayudyanti; Anik Nur Kholifah; Tomi Indarto; Darin Farah Nabilah; Mohammad Setyo Puji Raharjo (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This Normative Legal Study on PELAJAR (Peta Kebutuhan Pelatihan Kerja) Design in Gresik Regency examines the misalignment between national vocational paradigms and local industrial exigencies. Using statute and conceptual approaches, the study scrutinizes Presidential Regulation No. 68/2022 alongside regional mandates to identify regulatory gaps. Crucially, the quantitative metrics presented, such as the 60–65% efficacy rate, are normative analytical constructs reflecting the "degree of legal synchronization" rather than empirical statistical measurements. Findings reveal that the current PELAJAR design achieves only partial alignment, as centralized modules frequently marginalize hyperlocal imperatives such as petrochemical safety. This discrepancy creates a legislative vacuum that undermines the 60% local hiring quota mandated by Gresik's regulations, resulting in suboptimal labor absorption. The study concludes that the top-down framework risks normative obsolescence amidst regional expansion. Proposed reforms include institutionalizing a "Regional Synchronization Clause," introducing a "PELAJAR-Lokal Variant" with 40% of content customized, and implementing "Vocational Compliance Audits" under administrative court oversight. Such legislative restructuring is essential to transforming the PELAJAR blueprint into a dynamic instrument capable of achieving Indonesia's human capital vision within an 18-month roadmap.